Development of Jawara Values in Students for Preparing the Qualified Early Childhood Education Teachers - Asmawati, Luluk (Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2024)
This study examined how Jawara values were integrated into qualitative research methods courses. Sixty-four students participated, and the findings revealed that the procedural learning design successfully promoted these values. For instance, the majority of students demonstrated honesty, fairness, and respect for authority. However, there were areas for improvement, such as integrating qualitative research methods and mastering Indonesian spelling. Overall, the procedural learning design proved effective in fostering Jawara values and enhancing students' understanding of qualitative research.